(untitled) (Social and Environmental Law Journal, 2024)
Corporate Social Responsibility is deployed in a large part of organizations worldwide, which gives us the idea that companies are assuming dynamic social participation with comprehensive development plans in pursuit of improving the conditions of workers and the environment. and the final recipients, the consumers. Beyond the obligations that the company has with the State, CSR is presented as a voluntary contribution with which social, economic and environmental progress is sought, in order to generate an active contribution to society, creating positive added value for the organization. In this work we will focus on the facet related to the social dimension of the company’s activities. The approach will focus on the relationship between human rights, businesses and intersectionality. To do this, I propose to analyze a case decided on July 15, 2020 by the Inter-American Court of Human Rights entitled “Employees of the Santo Antônio de Jesus Fire Factory and their Relatives vs. Brazil". Through its analysis, we will reflect on different theoretical and practical categories: intersectionality, gender (in)equalities, labor discrimination, Drittwirkung theory, Stakeholder theory and the human right to sustainable development.